Nature of physicians' mistakes - F. F. Tetenev (Бюллетень сибирской медицины)
Diagnosis physicians' mistakes are inevitable which is due to peculiarities of clinical thinking associated with absence of specific symptoms and syndromes as concerns nosologic forms. Despite to introduction of high technologies, the development of early preclinical diagnosis possibilities and primary prevention of many diseases, value of traditional clinical methods of examination (questionnaires and physical examination ) not decreases but increases. To minimize physicians' mistakes and to decrease their consequences will help thorough theoretical training of the physician including knowledge of diagnosis theory, faultless mastering of traditional clinical methods of patient's examination and rational using of high diagnosis technologies.